Local administration of low-intensity vibration improves wound healing in diabetic mice - Roberts, Rita E.; Cavalcante-Silva, Jacqueline; Bilgen, Onur; Kineman, Rhonda D.; Koh, Timothy J. (Frontiers in Bioengineering and Biotechnology, 2026)
IntroductionChronic wounds related to diabetes incur significant morbidity and mortality, yet few effective therapies are available. Although whole body low-intensity vibration (LIV) has been shown to improve angiogenesis and wound healing in diabetic mice, local application of LIV signals could enhance the utility of this therapeutic approach.MethodsThe purpose of the present study was to compare the effectiveness of different treatment regimens involving local LIV applied to wounds of diabetic mice via oscillating motor, or by a wearable piezoelectric device.ResultsLocal LIV delivered by oscillating motor enhanced angiogenesis, granulation tissue formation and wound closure to a similar degree for all vibration protocols tested. In addition, local LIV induced protocol-dependent increases in wound IGF1 and VEGF levels that did not necessarily correlate with the effects on healing. LIV delivered by piezoelectric disks involved accelerations that were an order of magnitude smaller than those delivered by the oscillating motor, but produced significant increases in angiogenesis and granulation tissue formation, with trends of enhanced wound closure. These changes were associated with increased VEGF but not IGF1 levels.DiscussionThese findings demonstrate that local delivery of LIV can enhance key aspects of diabetic wound healing, highlighting its potential as a non-invasive method for improving healing of chronic diabetic wounds.